Origins of Contrasteric π-Facial Selectivity in Epoxidations of Encumbered Tetrahydropyridines by a Bifunctional Peracid - Chen, Shuming; Wang, Sining; Houk, K. N. (Synlett, 2019)
The origins of contrasteric diastereoselectivity in the epoxidation of encumbered tetrahydropyridines have been elucidated via density functional theory (DFT) calculations. A strong energetic preference for OH···N hydrogen bonding was found for epoxidation transition states of the unsubstituted tetrahydropyridine. For hexasubstituted tetrahydropyridines, the diastereofacial selectivity is dictated by both the strong OH···N hydrogen bonding and the conformational preference of the tetrahydropyridine substrate.
Keywords: DFT calculation; heterocycles; piperidines; epoxidation; stereoselective synthesis